Teachers Talking in Very Young Learners Immersion Class: How They Did It - Farouq Aji Subroto; Yazid Basthomi; Utari Praba Astuti (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This research aimed to describe the language used by the teachers namely teacher talk in VYL English Immersion class whose students’ age ranges from three to six years old and to describe how the language was used effectively in the class. The results showed that there were four types of teacher talk used frequently to help the teachers teach effectively in the class namely (1) giving directions, (2) giving information, (3) asking questions, and (4) praising and encouraging. Those four talks did not work alone in the class; the teachers also use gesture and demonstration to accompany the talks.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan tipe-tipe bahasa Inggris yang digunakan guru dalam konteks pengajaran bahasa Inggris pada kelas imersi dengan siswa berusia antara tiga sampai enam tahun dan menjelaskan bagaimana tipe-tipe bahasa tersebut digunakan secara efektif di kelas. Hasilnya, terdapat empat tipe bahasa yang sering digunakan guru untuk menyampaikan materi, yakni (1) pemberian arahan, (2) pemberian informasi, (3) pertanyaan, dan (4) pujian dan dorongan. Keempat tipe bahasa tersebut tidak digunakan secara independen di kelas. Guru juga menggunakan bahasa tubuh serta demonstrasi kegiatan saat menggunakan keempat tipe bahasa tersebut.